Tax Compliance and Tax Incentives during a Pandemic (Covid-19): Evidence from MSMEs in Indonesia (Universitas Muhammadiyah Yogyakarta, 2023)
The COVID-19 pandemic has significantly impacted Micro, Small, and Medium-sized Enterprises (MSMEs) by causing reduced demand, supply chain disruptions, cash flow issues, and digitalization challenges. To alleviate these challenges, governments have implemented tax incentives and relief measures. This study examines the factors influencing MSME taxpayer compliance with tax incentives during the COVID-19 pandemic. This study uses a quantitative approach with 167 respondents as MSME taxpayers in East Java, Indonesia. This study uses the SEM-PLS approach. Based on the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT), this study's results indicate a positive influence between attitude, subjective norm, Perceived Behavioral Control, and Self-efficacy on behavioral intention to tax compliance. It can be concluded that there is a positive relationship between behavioral intention to comply with taxes and tax compliance, which is moderated by tax incentives. This means that individuals who have a stronger intention to comply with taxes are more likely to actually comply, and this effect can be further strengthened by the provision of tax incentives.